Incidencia del liderazgo transformacional de las empresas familiares en la cohesión de grupo de sus empleados. - Teran Elizalde, Henry Mauricio (My University, 2019)
This research determines to what extent the group cohesion of employees from banana exporters in the Province of El Oro correlates with the degree of transformational leadership. The possible effects in the degree of leadership among the family generation may influence over the time the evolution of family businesses. This research results explained that among the studied enterprises, the years of a family business do not influence in group cohesion among their employees, but it was also found that the leadership of the management level does correlate with the cohesion of the employees, characteristic of banana exporters in Ecuador.
Esta investigación determina en qué medida la cohesión de grupo de los empleados de las empresas familiares de las exportadoras bananeras en la Provincia de El Oro - Ecuador se relaciona con el grado de liderazgo transformacional. Los posibles efectos en el grado de liderazgo entre las generaciones familiares pueden influenciar con el pasar del tiempo en la evolución de las empresas familiares. Los resultados de este estudio explicaron que, en las empresas estudiadas, los años de la empresa familiar no influyen con la cohesión de grupo entre sus empleados, sin embargo, los resultados arrojaron que el liderazgo de los jefes si se correlaciona con la cohesión de los empleados, característica de las exportadoras bananeras en Ecuador.
Keywords: EMPRESA FAMILIAR,; LIDERAZGO; LIDERAZGO TRANSFORMACIONAL; GENERACIÓN FAMILIAR,